Toward an integrated approach to nutritional quality, environmental sustainability, and economic viability: research and measurement gaps. (28th October 2014) - Herforth, Anna; Frongillo, Edward A.; Sassi, Franco; Mclean, Mireille Seneclauze; Arabi, Mandana; Tirado, Cristina; Remans, Roseline; Mantilla, Gilma; Thomson, Madeleine; Pingali, Prabhu
Abstract : Nutrition is affected by numerous environmental and societal causes. This paper starts with a simple framework based on three domains: nutritional quality, economic viability, and environmental sustainability, and calls for an integrated approach in research to simultaneously account for all three. It highlights limitations in the current understanding of each domain, and how they influence one another. Five research topics are identified: measuring the three domains (nutritional quality, economic viability, environmental sustainability); modeling across disciplines; furthering the analysis of food systems in relation to the three domains; connecting climate change and variability to nutritional quality; and increasing attention to inequities among population groups in relation to the three domains. For an integrated approach to be developed, there is a need to identify and disseminate available metrics, modeling techniques, and tools to researchers, practitioners, and policy makers. This is a first step so that a systems approach that takes into account potential environmental and economic trade‐offs becomes the norm in analyzing nutrition and food‐security patterns. Such an approach will help fill critical knowledge gaps and will guide researchers seeking to define and address specific research questions in nutrition in their wider socioeconomic and environmental contexts.